2022
DOI: 10.4209/aaqr.210324
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Trends, Profiles, and Exposure Risk of PM2.5-bound Bisphenol Analogs in Ambient Outdoor Air: A Study in Shanghai, China

Abstract: Fine particulate matter (PM2.5) possesses a larger surface area, which enables hazardous chemicals to adsorb. The particle can lodge deep in the lungs and bronchi of humans, causing diverse cardiovascular and respiratory diseases. PM2.5 exposure has significant socioeconomic repercussions as well as an increased risk of mortality. Some features of PM2.5 components have yet to be fully comprehended. PM2.5bound bisphenols (BPs), which mostly originate from the incineration of plastic waste, haven't been profound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…According to the physicochemical properties of BPA, the high potential for its presence could be occurred in the particulate matter (PM) of the urban atmosphere. However, few studies on the levels of PM-bound BPA in the atmospheric environment were reported in the literature [ 46 , 47 , 48 , 49 ]. Although there were no reports of the BPA levels in the ambient atmosphere of the Taiwan area, two studies were to determine the ambient BPA levels for workers in the BPA-containing plastic manufacturing industry and to evaluate the workers’ health risk [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the physicochemical properties of BPA, the high potential for its presence could be occurred in the particulate matter (PM) of the urban atmosphere. However, few studies on the levels of PM-bound BPA in the atmospheric environment were reported in the literature [ 46 , 47 , 48 , 49 ]. Although there were no reports of the BPA levels in the ambient atmosphere of the Taiwan area, two studies were to determine the ambient BPA levels for workers in the BPA-containing plastic manufacturing industry and to evaluate the workers’ health risk [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, discussions are still required to determine the applicability of the framework in studying plastic debris in all environments, including the atmosphere. The sampling of plastic particles in the atmosphere follows the established methods for sampling particulate matter (Dris et al, 2017b;Abbasi et al, 2019;Allen et al, 2019a;Chen et al, 2020;Beaurepaire et al, 2021;Ding et al, 2021;Munyaneza et al, 2022;Pan et al, 2022). Passive and active samplers have been used to sample atmospheric plastic debris in both indoor and outdoor air.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…BPA was detected at concentrations ≥1.4 ng.m −3 in 26 samples, reaching levels up to 3.03 ng.m −3 in PN2; however, it was not found in TH1, CG3, CG4, or CG8 (Table S1). BPA is released into the atmosphere via the combustion of plastics and has potential hepatotoxicity, neurotoxicity, and immunotoxicity, even at low concentrations [30,31]. Inhaling the other detected antioxidants, such as phenols, benzaldehyde, and benzoquinone derivatives, may cause headaches, nausea, or sore throat [32,33].…”
Section: Antioxidantsmentioning
confidence: 99%